SUCCESSFUL MANAGEMENT OF FOETAL MUMMIFICATION IN A CROSSBRED JERSEY COW- A CASE REPORT - U.S. Kalyaan; R. Rajalakshmi; S. Rangasamy; T. Sarath; K. Krishnakumar; R. Sureshkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Successful obstetrical management of foetal mummification in a full term pregnant pluriparous crossbred Jersey cow by per vaginal removal of foetal parts is reported and discussed.